Reframing Street-Level Bureaucracy through Resilience Governance in Disaster Contexts in Majene Regency - Ismail; Faisal Ardiansyah; Andi Anugrah Mahyuddin; Abd. Rahman Yus; Nurul Ayuni (International Journal Of Public Policy and Bureaucracy, 2025)
This study examines the role of street-level bureaucrats (SLBs) in resilience governance, using the 2021 earthquake in Majene Regency, Indonesia, as a critical case. Moving beyond conventional interpretations of discretion as merely a reactive coping mechanism, the article reconceptualizes SLB discretion as a strategic capacity embedded within institutional resilience. Drawing on qualitative methods—semi-structured interviews, field observations, and document analysis—the study identifies how SLBs enact three forms of resilience capacity: absorptive, adaptive, and transformative. These roles enable SLBs to respond effectively to uncertainty, resource constraints, and procedural rigidity. Theoretically, the article advances the integration of resilience governance and street-level implementation theory by proposing an analytical framework that maps SLB practices across key dimensions of resilience. Empirically, the findings show that SLBs operate as informal first responders, adapting disaster policies in real time through the use of discretion, tacit knowledge, and social networks to bridge gaps between centralized systems and local needs. The study recommends formal recognition of SLB discretion through adaptive standard operating procedures (SOPs), flexible budgeting arrangements, and decentralized coordination mechanisms. Strengthening SLB institutions, underpinned by trust and institutional flexibility, can enhance the agility of the public sector. Overall, the findings offer conceptual and practical guidance for integrating local institutions into national resilience frameworks, particularly in fragile and disaster-prone settings across the Global South.